O Federal Reserve antes da crise: análise da política monetária e das percepções do Fed entre 2001 e 2007 por meio de sua comunicação - Ferrara, Daniel Nicolau (2011)
In the analysis of the origins of the severe financial crisis, which began in 2007 in the US, remains an open debate about the reasons that led the Fed to underestimate the severity of the crisis. This study analyzes the perceptions of Central Bank on the peculiar context that has developed from 2001. The economic recovery was based on consumption and housing market, including the income extraction derived from valued housing, and followed by the risk of deflation, which subsequently led to growing fears about what was happening in the markets. The instrument used for this is the thorough analysis of the minutes of the FOMC and the pronouncements of the two presidents of the Fed, from 2001 to 2007, Greenspan and Bernanke, in addition to theoretical concepts and economic problems of that period. The methodology is justified because the communication with the market has become a relevant instrument in the Fed's action since the 1990s. The analysis of documents showed that in the aftermath of the crises of 2001-2002, the Fed used to acknowledge consumption and housing market to be important forces in the economic recovery. From 2003-2004, the FOMC members showed concern about the speculative behavior in housing and the effects of the reversal of the expansionary monetary policy would have on property prices and on consumption. The Fed's action to combat these threats was restrained by the belief in the strength of the deregulated financial system, by pragmatic confidence in the conduct of monetary policy guided by the risk management approach and the belief that Central Bank should not act against the formation of bubbles